2020
DOI: 10.1177/1362361320918754
|View full text |Cite
|
Sign up to set email alerts
|

Considering efficacy and effectiveness trials of cognitive behavioral therapy among youth with autism: A systematic review

Abstract: Cognitive behavioral therapy is a widely studied and commonly used psychosocial intervention for treating emotional problems in individuals with autism. To date, most studies of cognitive behavioral therapy and autism have focused on efficacy. Effectiveness trials, by contrast, measure whether an intervention produces particular results under “real-world” clinical conditions. We conducted a systematic review of cognitive behavioral therapy interventions targeting affective disorders among youth with autism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Consistent with prior reviews examining mental health interventions for ASD (e.g. Keefer et al, 2018;Lake et al, 2020), the primary mental health problems or conditions targeted were internalizing problems (primarily anxiety) and challenging behaviors. Interventions developed specifically for ASD more frequently targeted externalizing or transdiagnostic problems, such as challenging behaviors, compared to those adapted for ASD, where anxiety was more frequently targeted.…”
Section: Intervention Informationmentioning
confidence: 62%
See 3 more Smart Citations
“…Consistent with prior reviews examining mental health interventions for ASD (e.g. Keefer et al, 2018;Lake et al, 2020), the primary mental health problems or conditions targeted were internalizing problems (primarily anxiety) and challenging behaviors. Interventions developed specifically for ASD more frequently targeted externalizing or transdiagnostic problems, such as challenging behaviors, compared to those adapted for ASD, where anxiety was more frequently targeted.…”
Section: Intervention Informationmentioning
confidence: 62%
“…Many interventions reviewed reported adapting existing mental health EBIs for use with ASD. CBT, CBT-based, and behavioral parent training interventions were the most frequently adapted EBIs, which is similarly reflected by these approaches' large representation within the broader children's mental health services literature, including those specifically pertaining to ASD (Keefer et al, 2018;Lake et al, 2020). ASD-specific adaptations were more common than general adaptations, with the most common goal or intent of adaptations to tailor for ASD characteristics.…”
Section: Intervention Adaptationsmentioning
confidence: 94%
See 2 more Smart Citations
“…In line with a previous systematic review [ 24 ], our results showed that access to ASD services is a relevant protective factor not only for children, but also for parents [ 40 ]. Children with ASD can be expected to gain significant improvements when diagnosed early and when engaged in structured, intensive, evidence-based programs [ 61 , 62 , 63 ]. In contrast, difficulties in meeting the service needs of children with ASDs, ranging from general medical services to supportive services [ 64 ], can generate a vicious cycle of worsening symptoms and an overload of responsibility on parents who come to feel exhausted and ineffective [ 39 ].…”
Section: Discussionmentioning
confidence: 99%